Implementasi Pembelajaran Bahasa Inggris Materi Parts of Body Melalui Media Lagu pada Siswa Kelas IV-D di SDN 060871 Medan Timur” - Nanda Ramadani; Putri Nabila Azzahra Hasibuan; Helena Raymonda Sipayung; Cucu Tri Ayu Ningrum; Mita Maharani Berutu; Andini Herlambang (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
This study explores the application of English education focused on the topic of body parts, utilising musical resources as a supplementary tool for students in class IV-D at SDN 060871 Medan Timur. The research method used is quantitative with an experimental design through pre-test and post-test to determine the effectiveness of song media in improving English vocabulary mastery. The research results showed that before the application of song media, student learning outcomes were in the poor category with a completeness level of 54.54%. After implementing song media, there was an increase in student learning outcomes until they reached a completion level of 90.90%. This demonstrates that utilising music can aid learners in grasping and retaining English vocabulary with greater efficiency. Apart from that, the results of the confirmation questionnaire also showed that the majority of students gave positive responses to the application of song media in learning English. Therefore, song media can be used as an alternative learning method that is interesting and effective in improving student learning outcomes in mastering English vocabulary.